Three Day Week - leaflet, 1973 (London, 1973)
1973 1970-74 "Three Day Week - leaflet, 1973" [BW0187], 1973, Trades Union Congress Phase 3 of the Conservative Government's incomes policy, which included limiting pay raises to 7%, was launched in November 1973. On 12 November, the National Union of Mineworkers started a national overtime ban and on the following day, the Government declared a State of Emergency. A month later, the Government announced that three day working would start on 1 January 1974. Working hours were cut to conserve available fuel stocks for electricity. The Three Day Week officially ended 7 March 1974.